A methodology for knowledge acquisition through literature: Building knowledge-based systems for strategic management - Andreas Lehmann (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1991)
In this paper a methodology designed for knowledge acquisition through literature is presented. It mainly fits strategic business problems, but is also applicable in domains with similar characteristics. In contrast to other methodologies that use documents in textual forms, this approach tries to incorporate public knowledge to a large extent. In several subsequent steps this knowledge is elicited, documented, evaluated and formalized. The result of this methodology is a formalized and structured knowledge document that is well-prepared for implementation in a rule-based KBS. Emphasis is laid on problems concerning the evaluation and interpretation of the content rather than on technical problems arising in this context. Implementation, testing and verification of the knowledge base are subsequent stages to occur after knowledge acquisition and are not described within this paper.
Keywords: 650; Expertensystem; Theorie